Maternal serum ischemia modified albumin as a marker for hypertensive disorders of pregnancy: a pilot study - Vyakaranam, Sapna; Bhongir, Aparna Varma; Patlolla, Dakshayani; Chintapally, Rekha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Hypoxia driven oxidative stress of the placenta contributes to the pathogenesis of preeclampsia. Serum Ischemia Modified Albumin (IMA) has recently emerged as an oxidative stress marker, used in diagnosis of cardiac ischemia. Aim: To determine the efficiency of serum IMA in differentiating hypertensive disorders of pregnancy (pregnancy induced hypertension, preeclampsia) from normal pregnancy. Methods: It was a case control study. Pregnant women ≥32 weeks of gestation. Study population were included 3 groups, 19 Normotensive Pregnant (NP) women as controls, 18 pregnant women with Pregnancy Induced Hypertension (PIH) and 19 with preeclampsia (PE). Serum IMA was estimated by Enzyme Linked Immune Sorbent Assay (ELISA). Results were analyzed by student ‘t’test. Critical values for serum IMA were obtained by Receiver Operation Characteristics (ROC) curves. Results: Serum IMA levels were significantly elevated in PE (56.84 ± 21.57 ng/ml) when compared with PIH (36.24 ± 14.51 ng/ml) and NP (35.47 ± 11.58 ng/ml) (P value <0.001). With a cutoff of 38.33 ng/ml, sensitivity and specificity for preeclampsia was 88.9% and 73.7% respectively. Conclusions: Our study demonstrated that serum IMA, an oxidative stress marker is elevated in PE & PIH. Hence serum IMA can undergo further evaluation as a marker of PE.